Forensic Technology and Crime Management in Nigeria: A Study of Rivers State - Aaron, Anyanabia (2019)
In Developed Countries (DCs) of the world adoption of scientific sophistication in crime management and investigation has advanced tremendously. This has led to unravelling of criminal syndicates and all forms of crime, and has also established incontrovertible act and legally admissible evidences before the court. Unfortunately the reverse is the case in Nigeria, following the inability of the government to provide the security agencies with modern equipment, such as a more functional and efficient database for criminal records and enough trained professionals. The Country’s Central Criminal Registry (CCR) still makes use of outdated manually kept records, thus making it difficult to assess the fingerprints of more than one hundred and fifty million people. It is therefore, in the interest of the researchers to critically examine the roles, challenges and prospects of forensic technology in crime management and control in Nigeria with a focus on Rivers State as well as to proffer relevant solutions to the already biting situation. The study found it necessary to adopt explorative and descriptive design since it is used in obtaining data/information related to the current status of the phenomena to be described or under investigation. The study adopted “Social Constructionist Theory” and “The Role Theory” to evaluate the relationship between the variables in the study. The findings showed that combating crime through forensic technology is eminent and sacrosanct but in Nigeria the reverse is the case hence protracted crime, insurgency and insecurity. It recommends that in view of technological advancement, government should integrate technology and specialist field training into crime management programme that will place security personnel ahead of criminals which will definitely create a robust national security and development. Keywords: Forensic, Technology, Crime Management in Nigeria DOI: 10.7176/RHSS/9-14-06 Publication date:July 31st 201